Signifikansi Maqâṣid al-Sharîah sebagai Kerangka Berpikir Epistemik Ijtihad - Sanuri Sanuri (Islamica: Jurnal Studi Keislaman, 2014)
This paper focuses on the importance of maqâṣid al-sharîah for the effectiveness of ijtihad in Islamic law. The emergence of controversies at the beginning of the tenth century AD on the issue of the closing of the gate of ijtih?d has resulted in the rigidity of Islamic law and its methodological framework. Along with these issues, some contemporary scholars on maqâṣid agreed that al-sharîah law (al-Qurân) consists of partial (juzîyât) and universal values (kullîyyât) that should be understood through a holistic approach in the frameworks of maq?sid. Shift in the meaning and orientation of maqâṣid al-sharîah in some contemporary Muslim scholars? views, involving social sciences, philosophy of law, principles of morality, universality, social justice, human dignity, human rights, is a concrete manifestation of how Islamic law is able to provide answers to the current problems faced by the Muslim and non-Muslims community. This awareness has made contemporary Muslim thinkers strive to bring Islamic law into various achievements of progress in many aspects of life by emphasizing the importance of maqâṣid al-sharîah.